EFL Reading Metacomprehension from the Developmental Perspective: A Longitudinal Case - Renata Šamo; Alenka Mikulec (National Research University Higher School of Economics, 2018)
As the first half of the literacy equation (reading + writing = literacy), reading is primarily considered a dynamic meaning-focused interaction in which the reader is required to build comprehension of a text in a non-linear way. In other words, the reader is constantly checking the degree to which he or she understands the given information, simultaneously trying to identify comprehension failures and employ efficient repair strategies. This ability is termed metacomprehension; when it is enhanced, comprehension is generally more successful. Metacomprehension appears to be even more important for non-native readers because of their limited vocabulary and grammar. This is the key theoretical background of the single case study described in the current paper since it follows the developmental path of an EFL learner (Croatian teenager) with special focus on his reading ability. The main aim of the study was to see how his metacomprehension would develop over an extended period of exposure to EFL in the school setting. It was based on the hypothesis that extended exposure would result in better awareness of comprehension during the reading process. The study was conducted in two parts (Grade 5 and Grade 8) and comprised a number of stages. Being a case study, multiple sources and techniques were applied in gathering data, both qualitative and quantitative, such as: a multiple-choice comprehension test, a questionnaire for measuring the reader's awareness of strategic reading processes (in Grade 5), an English proficiency test, a text restoration task, the self-revelation (stream-of-consciousness data) technique, a post-reading interview, and observation notes (in Grade 8). The results obtained initially indicated the participant's good EFL reading comprehension performance but later showed that he was less successful, which was related to his poor EFL proficiency. In terms of reading strategy, it can be added that, despite some initial strategic abilities, the participant did not significantly develop his strategic behaviour for EFL reading. To conclude, prolonged exposure to EFL did not lead to better reading metacomprehension in this particular school learner.